Adverse Drug Reactions Causing Admission to Medical Wards: A Cross-Sectional Survey at 4 Hospitals in South Africa. Issue 19 (May 2016) - Mouton, Johannes P.; Njuguna, Christine; Kramer, Nicole; Stewart, Annemie; Mehta, Ushma; Blockman, Marc; Fortuin-De Smidt, Melony; De Waal, Reneé; Parrish, Andy G.; Wilson, Douglas P.K.; Igumbor, Ehimario U.; Aynalem, Getahun; et al.
Abstract : Abstract: Limited data exist on the burden of serious adverse drug reactions (ADRs) in sub-Saharan Africa, which has high HIV and tuberculosis prevalence. We determined the proportion of adult admissions attributable to ADRs at 4 hospitals in South Africa. We characterized drugs implicated in, risk factors for, and the preventability of ADR-related admissions. We prospectively followed patients admitted to 4 hospitals' medical wards over sequential 30-day periods in 2013 and identified suspected ADRs with the aid of a trigger tool. A multidisciplinary team performed causality, preventability, and severity assessment using published criteria. We categorized an admission as ADR-related if the ADR was the primary reason for admission. There were 1951 admissions involving 1904 patients: median age was 50 years (interquartile range 34–65), 1057 of 1904 (56%) were female, 559 of 1904 (29%) were HIV-infected, and 183 of 1904 (10%) were on antituberculosis therapy (ATT). There were 164 of 1951 (8.4%) ADR-related admissions. After adjustment for age and ATT, ADR-related admission was independently associated ( P ⩽ 0.02) with female sex (adjusted odds ratio [aOR] 1.51, 95% confidence interval [95% CI] 1.06–2.14), increasing drug count (aOR 1.14 per additional drug, 95% CI 1.09–1.20), increasing comorbidity score (aOR 1.23 per additional point, 95% CI 1.07–1.41), and use of antiretroviral therapy (ART) if HIV-infected (aOR 1.92 compared with HIV-negative/unknown, 95% CI 1.17–3.14). The most common ADRs were renal impairment, hypoglycemia, liver injury, and hemorrhage. Tenofovir disoproxil fumarate, insulin, rifampicin, and warfarin were most commonly implicated, respectively, in these 4 ADRs. ART, ATT, and/or co-trimoxazole were implicated in 56 of 164 (34%) ADR-related admissions. Seventy-three of 164 (45%) ADRs were assessed as preventable. In our survey, approximately 1 in 12 admissions was because of an ADR. The range of ADRs and implicated drugs reflect South Africa's high HIV and tuberculosis burden. Identification and management of these ADRs should be considered in HIV and tuberculosis care and treatment programs and should be emphasized in health care worker training programmes. Abstract : Supplemental Digital Content is available in the text